Face-/Edge-Shared 3D Perovskitoid Single Crystals with Suppressed Ion Migration for Stable X-Ray Detector - Zhang, Zimin; Wang, Xiaoli; Li, Huayang; Li, Dong; Zhang, Yang; Shen, Nan; Yu, Xue‑Feng; Liu, Yucheng; Liu, Shengzhong; Song, Haomin; Liu, Yanliang; Wang, Xingzhu; et al. (Nano-Micro Letters, 2025)
Although three-dimensional metal halide perovskites are promising candidates for direct X-ray detection, the ion migration of perovskites seriously affects the detector stability. Herein, face-/edge-shared 3D heterometallic glycinate hybrid perovskitoid Pb2CuGly2X4 (Gly = -O2C-CH2-NH2; X = Cl, Br) single crystals (SCs), in which the adjacent lead halide layers are linked by large-sized Cu(Gly)2 pillars, are synthesized in water. The Cu(Gly)2 pillars in combination with face-/edge-shared inorganic skeleton are found able to synergistically suppress the ion migration, delivering a high ion migration activation energy (Ea) of 1.06 eV. The Pb2CuGly2Cl4 SC X-ray detector displays extremely low dark current drift of 1.20 × 10–9 nA mm−1 s−1 V−1 under high electric field (120 V mm−1) and continuous X-ray irradiation (2.86 Gy), and a high sensitivity of 9,250 μC Gy−1 cm−2 is also achieved. More excitingly, the Pb2CuGly2Cl4 nanocrystal can be easily dispersed in water and directly blade-coated on thin-film transistor (TFT) array substrate, and the obtained Pb2CuGly2Cl4-based TFT array detector offers an X-ray imaging capability with spatial resolution of 2.2 lp mm−1. Highlights: 1 3D perovskitoid Pb2CuGly2X4 (Gly = -O2C-CH2-NH2; X = Cl, Br) single crystals (SCs) with face-/edge-shared inorganic skeleton and CuGly2 pillars delivered a high ion migration activation energy of 1.06 eV. 2 The Pb2CuGly2Cl4 SC X-ray det cector presented low dark current drift (1.20 × 10–9 nA mm−1 s−1 V−1 at 120 V mm−1) and high sensitivity (9250 μC Gy−1 cm−2). 3 The Pb2CuGly2Cl4 film-based thin-film transistor array detector offered an X-ray imaging capability with spatial resolution of 2.2 lp mm−1.